Combination of App-Based Ultrasound Simulation and Conventional Learning Methods in Medical Education for Fetal Echocardiography - Hartmann, Tim; Adiyaman, Duygu; Lato, Christiane; Janni, Wolfgang; Hartmann, Julien; Lato, Krisztian (Ultraschall in der Medizin - European Journal of Ultrasound)
Purpose: This study examines whether combining conventional textbook materials with the app-based ultrasound simulator Scanbooster enhances learning outcomes in fetal echocardiography, compared to using either method alone. It also evaluates the impact of the learning sequence. Materials and Methods: 210 medical students were randomized into two groups: • PDF→App Group (n=103): Textbook study followed by the Scanbooster ultrasound simulator app • App→PDF Group (n=107): Scanbooster ultrasound simulator app followed by textbook study Knowledge was assessed before and after by identifying marked structures in ultrasound videos. Results: There were no significant differences between the groups regarding age (p=0.564) and prior ultrasound experience (p=0.746). Both groups showed a significant improvement in identifying sonographic structures after the learning phase (p<0.001), with a mean learning effect of 104.96% and 102.16%, respectively, for fetal echocardiography- specific knowledge. The order of learning materials had no significant effect on learning success (p>0.05). In comparison with our previous study, we found that the combination of app-based simulation and textbooks led to the best learning outcomes in fetal echocardiography. This approach resulted in significantly higher performance compared to pure PDF learning (p<0.001) and was slightly, yet still significantly better than pure simulation (p=0.031). Conclusion: The combination of conventional textbook material and app-based ultrasound simulation is the most effective approach for teaching fetal echocardiography. The learning sequence does not significantly impact the outcome.